Impact of Personal Protective Equipment on Surgical Performance During the COVID-19 Pandemic - Yánez Benítez, Carlos (World J Surg, 2020)
BACKGROUND: The Severe Acute Respiratory Syndrome Coronavirus 2 pandemic has exposed surgeons to hazardous working conditions, imposing the need for personal protective equipment (PPE) use during surgery. The use of such equipment may affect their non-technical skills, augment fatigue, and affect performance. This study aimed to assess the surgeons’ perceptions of the impact of wearing PPE during emergency surgery throughout the pandemic. METHODS: An international cooperation group conducted an anonymous online survey among surgeons from over 30 countries, to assess perceptions about the impact of PPE use on non-technical skills, overall comfort, decision making, and surgical performance during emergency surgery on COVID-19 patients. RESULTS: Responses to the survey (134) were received from surgeons based on 26 countries. The vast majority (72%) were males. More than half of the respondents (54%) felt that their surgical performance was hampered with PPE. Visual impairment was reported by 63%, whereas 54% had communication impediments. Less than half (48%) felt protected with the use of PPE, and the same proportion perceived that the use of such equipment influenced their decision making. Decreased overall comfort was cited by 66%, and 82% experienced increased surgical fatigue. CONCLUSIONS: Surgeons perceived impediment for both visibility and communication, and other non-technical skills while using PPE on emergency surgery in COVID-19 patients. Their perceived lack of protection and comfort and increased fatigue may have inhibited their optimal surgical performance. More attention should be placed in the design of more user-friendly equipment, given the possibility of a second wave of the pandemic.